Asian development outlook 2018 how technology affects jobs. (Asian Development Outlook Series., 2018)
The theme chapter of this years ADO explores technology and jobs. While new technologies will displace certain types of jobs, rising demand and higher output will create jobs, and new occupations and industries will emerge.Developing Asia is forecast to expand by 6.0% in 2018, and by 5.9% in 2019. Excluding Asias high income newly industrialized economies, growth should reach 6.5% in 2018 and 6.4% in 2019. With oil prices edging up and robust consumer demand continuing, inflation is poised to pick up after dipping slightly last year. Consumer prices are projected to rise by 2.9% in both 2018 and 2019, or 0.6 percentage points more than in 2017. Though prospects are firm, risks are clearly to the downside. Protectionist measures and retaliation against them could undermine the recent pickup in trade growth. In response to fiscal stimulus, the United States Federal Reserve may need to raise interest rates faster than currently expected, which could diminish capital flows to developing Asia.